Penyuluhan dan Pemeriksaan Asam Urat pada Lansia di Panti Werdha Damai Ranomuut Manado : Penelitian - Puspita Ningrum; Erna Purwanti; Junytha Rondonuwu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Uric acid is one of the main causes of chronic inflammatory arthritis in Indonesia, characterized by the deposition of monosodium urate (MSU) monohydrate crystals in the tissues. Gouty arthritis is a non-communicable disease often experienced by elderly people caused by a lack of understanding about foods that have high purine content. The purpose of writing this article is to determine the normal levels of uric acid in the elderly. This community service was carried out at the Damai Ranomuut Manado Werdha Panti with a total of 35 elderly people. The methods used were counseling and uric acid examination. The results showed that 16 elderly people had high uric acid levels, consisting of 14 women and 2 men.